Central retinal artery occlusion as a neuro-ophthalmological emergency: the need to raise public awareness - Hoyer, Carolin; Kahlert, Christian; Güney, Resul; Schlichtenbrede, Frank; Platten, Michael; Szabo, Kristina (European journal of neurology, 2021)
Background and purpose Central retinal artery occlusion (CRAO) is a neuro-ophthalmological emergency necessitating adequate and comprehensive diagnosis. Its optimal management and treatment, however, are still under debate. This study aimed at identifying respective areas for improvement. Methods We retrospectively analysed the medical records of patients with CRAO treated in our stroke unit between January 2016 and August 2020. Results During the observational period, 101 patients with CRAO were admitted. We observed an increase in the rate of patients primarily admitted to the stroke unit from 52.2% to 97.4%. In addition, the thrombolysis rate - with thrombolysis performed on an individual basis - rose from 0% to 14.1%, coinciding with the implementation of an in-hospital management guideline. Almost 60% of all patients presented outside of the 4.5-h time window for thrombolysis; by far the most common reason not to deliver intravenous thrombolysis in our cohort was a prehospital delay to presentation (58.8%), with 44.4% of patients having consulted a private-practice ophthalmologist first. A total of 25 (32.5%) of 77 patients who underwent magnetic resonance imaging (MRI) had accompanying acute ischaemic stroke lesions on diffusion-weighted MRI of the brain. A possible aetiology of CRAO was identified in 41.4% of patients. Discussion Public awareness of sudden unilateral visual loss as a presenting sign for stroke should be raised, increasing the chances for timely recognition in a hospital with ophthalmological expertise and a stroke centre. This is essential for ongoing and future prospective trials on this subject.